Opposite effects of tamoxifen on metabolic syndrome‐induced bladder and prostate alterations: A role for GPR30/GPER?. Issue 1 (26th August 2013) - Comeglio, P.; Morelli, A.; Cellai, I.; Vignozzi, L.; Sarchielli, E.; Filippi, S.; Maneschi, E.; Corcetto, F.; Corno, C.; Gacci, M.; Vannelli, G.B.; Maggi, M.
Abstract BACKGROUND BPH and LUTS have been associated to obesity, hypogonadism, and metabolic syndrome (MetS). MetS‐induced prostate and bladder alterations, including inflammation and tissue remodeling, have been related to a low‐testosterone and high‐estrogen milieu. In addition to ERs, GPR30/GPER is able to mediate several estrogenic non‐genomic actions. METHODS Supplementing a subgroup of MetS rabbits with tamoxifen, we analyzed the in vivo effects on MetS‐induced prostate and bladder alterations. The effects of selective ER/GPER ligands and GPER silencing on prostate inflammation were also studied in vitro using hBPH cells. RESULTS ERα, ERβ, and PR expression was upregulated in MetS bladder, where tamoxifen decreased ERα and PR expression, further stimulating ERβ. In addition, tamoxifen‐dosing decreased MetS‐induced overexpression of inflammatory and tissue remodeling genes. In prostate, sex steroid receptors, pro‐inflammatory and pro‐fibrotic genes were upregulated in MetS. However, tamoxifen did not affect them and even increased COX‐2. In hBPH cells, 17β‐estradiol increased IL‐8 secretion, an effect blunted by co‐treatment with GPER antagonist G15 but not by ER antagonist ICI 182, 780, which further increased it. GPER agonist G1 dose‐dependently (IC50 = 1.6 nM) induced IL‐8 secretion. In vitro analysis demonstrated that GPER silencing reverted these stimulatory effects. CONCLUSIONS GPER can be considered the main mediator of estrogen action in prostate, whereas in bladder the mechanism appears to rely on ERα, as indicated by in vivo experiments with tamoxifen dosing. Limiting the effects of the MetS‐induced estrogen action via GPER could offer new perspectives in the management of BPH/LUTS, whereas tamoxifen dosing showed potential benefits in bladder. Prostate 74:10–28, 2014. © 2013 Wiley Periodicals, Inc.